An anti-freezing wearable strain sensor based on nanoarchitectonics with a highly stretchable, tough, anti-fatigue and fast self-healing composite hydrogel. (September 2022) - Wang, Yanqing; Pang, Bo; Wang, Rixuan; Gao, Yiliang; Liu, Yuetao; Gao, Chuanhui
Graphical abstract: Abstract: The application of conductive hydrogel sensors in wearable devices and electronic skin has aroused great research interest. However, hydrogel sensor cannot simultaneously have good self-healing properties, anti-freezing properties and excellent anti-fatigue properties, which results in poor reusability and unstable sensing performance. A composite hydrogel was synthesized by one-pot method using polyvinyl alcohol, acrylamide, sodium alginate and glycerol as raw materials. The obtained hydrogel has excellent mechanical properties (0.51 MPa stress, 1500% elongation at break and tensile toughness of 3.6 MJ/m 3 ) and fast self-healing performance with healing efficiency (HE) as high as 92% without any external stimulus. At the same time, glycerol has strong freeze resistance for hydrogels. The hydrogel can stably transmit electrical signals at subzero temperature (−20 °C). In addition, we also verified that the hydrogel could self-recover in a short time through cyclic stretching, indicating the fatigue resistance and rapid recovery of the material.